Risk factors of acute renal impairment after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. (1st January 2020) - Chen, Chao-Yu; Chang, Hung-Yu; Lu, Chang-Hsien; Chen, Min-Chi; Huang, Tzu-Hao; Lee, Li-Wen; Liao, Yu-San; Chen, Vincent Chin-Hung; Huang, Wen-Shih; Ou, Yu-Che; Lung, Feng-Chi; Wang, Ting-Yao
Abstract: Background: Acute renal impairment (ARI) is a major complication after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) for cancer patients with peritoneal metastases. This study aimed to investigate the incidence and identify the risk factors of post-HIPEC creatinine increased. Methods: From April 2015 to December 2019, demographic and perioperative data of 169 patients undergoing CRS/HIPEC with a preoperative creatinine level <1.5 mg/dL were retrospectively reviewed. Renal impairment was defined according to the National Cancer Institute Common Terminology Criteria for Adverse Events (NCI-CTCAE) version 5.0. The risk factors of creatinine increased were analyzed using univariate and multiple logistic regression analyses. Results: Among the 169 enrolled patients, 21 (12.4%) had postoperative creatinine increased (ARI group) and 148 (87.6%) did not (non-ARI group). Significantly more of the ARI group received a cisplatin HIPEC regimen than the non-ARI group (71.4 vs. 37.8%, p  = 0.004). Multiple logistic regression analysis revealed that the patients who received a cisplatin HIPEC regimen (adjusted odds ratio [AOR] = 11.38, p  < 0.001) and peritoneal dialysis solution as HIPEC perfusate (AOR = 7.07, p  = 0.002) were more likely to develop post-HIPEC creatinine increased. Conclusions: Identifying the risk factors of post-HIPEC creatinine increased can help to improve patient selection, a dose of HIPEC regimens modification and perioperative care. We also identified the detrimental renal effect of peritoneal dialysis solution as HIPEC perfusate. More prospective studies are warranted to confirm these findings.